Transcriptomic profiling revealed the role of 24-epibrassinolide in alleviating salt stress damage in tall fescue (Festuca arundinacea) - Chen, Yao; Xiang, Yuanhang; Hu, Zhengrong; Gao, Yang; Zhang, Youxin; Chen, Minghui; Khaldun, A. B. M.; Yan, Xuebing; Fan, Jibiao (Frontiers in Plant Science, 2022)
Soil salinization is a major problem all over the world. The accumulation of salt in soil reduces the root water uptake and directly affects plant growth and metabolic activities. Brassinosteroid is a plant hormone that plays an important role in regulation of plant growth and physiological process, including promotion of cell expansion and elongation, signal transduction and stress response. Exogenous 24-epibrassinolide (EBL) has been proved to alleviate various environmental stress in plants. However, the role that EBL plays in salt stress response is still unknown in tall fescue (Festuca arundinacea). In this study, the physiology and molecular mechanisms regulated by exogenous EBL of salt stress response in tall fescue was investigated. Tall fescue plants were divided into four groups, including control (CK), NaCl solution (SALT), 24-epibrassinolide (EBL), NaCl solution + 24-epibrassinolide (SE). During the growth period of tall fescue, we took several samples to determine the physiological indexes. We found that electrolyte leakage (EL) and malondialdehyde (MDA) were decreased, chlorophyll (Chl) content and antioxidant enzyme activity were increased in leaves of tall fescue treated with EBL under NaCl stress. Transcriptomic profiling analysis showed that after 12 h of treatments, 10,265, 13,830 and 10,537 differential genes were expressed in EBL, SALT and SE groups compared with control, respectively. These differentially expressed genes mainly focused on binding, catalytic activity, cellular process, metabolic process, cellular anatomical entity. Moreover, most of the differential genes were expressed in the plant hormone signal transduction pathway. These results helped us to better understand the mechanism of exogenous 24-epibrassinolide to improve the salt tolerance of tall fescue.